Crataegus Extract WS®1442 Stimulates Cardiomyogenesis and Angiogenesis From Stem Cells: A Possible New Pharmacology for Hawthorn? - Halver, Jonas; Wenzel, Kristin; Sendker, Jandirk; Carrillo García, Carmen; Erdelmeier, Clemens A. J.; Willems, Erik; Mercola, Mark; Symma, Nico; Könemann, Stephanie; Koch, Egon; Hensel, Andreas; Schade, Dennis (Frontiers in Pharmacology, 2019)
Extracts from the leaves and flowers of Crataegus spp. (i.e., hawthorn species) have been traditionally used with documented preclinical and clinical activities in cardiovascular medicine. Based on reported positive effects on heart muscle after ischemic injury and the overall cardioprotective profile, the present study addressed potential contributions of Crataegus extracts to cardiopoietic differentiation from stem cells. The quantified Crataegus extract WS®1442 stimulated cardiomyogenesis from murine and human embryonic stem cells (ESCs). Mechanistically, this effect was found to be induced by promoting differentiation of cardiovascular progenitor cell populations but not by proliferation. Bioassay-guided fractionation, phytochemical and analytical profiling suggested high-molecular weight ingredients as the active principle with at least part of the activity due to oligomeric procyanidines (OPCs) with a degree of polymerization between 3 and 6 (DP3-6). Transcriptome profiling in mESCs suggested two main, plausible mechanisms: These were early, stress-associated cellular events along with the modulation of distinct developmental pathways, including the upregulation of brain-derived neurotrophic factor (BDNF) and retinoic acid as well as the inhibition of Transforming Growth Factor /Bone Morphogenetic Protein (TGF/BMP) and Fibroblast Growth Factor (FGF) signaling. In addition, WS®1442 stimulated angiogenesis ex vivo in Sca-1+ progenitor cells from adult mice hearts. These in vitro data provide evidence for a differentiation promoting activity of WS®1442 on distinct cardiovascular stem/progenitor cells that could be valuable for therapeutic heart regeneration after myocardial infarction. However, the in vivo relevance of this new pharmacological activity of Crataegus spp. remains to be investigated and active ingredients from bioactive fractions will have to be further characterized.